SCHIZOPHRENIA OF MAIN CHARACTER IN BEAUTIFUL MIND MOVIE DIRECTED BY RON HOWARD - Unpris Yastanti; Emma Soraya (LPPM Universitas Bina Sarana Informatika, 2016)
The objective of this study is to identify schizophrenia of the main character, John Nash in Beautiful Mind movie directed by Ron Howard. This study used descriptive method to analyze data. The study revealed the following findings: (1) The type schizophrenia of main character is Paranoid schizophrenia.(2) The effects of schizophrenia of John Nash are life disruption and substance abuse. John does something abnormal, he speaks with people who is not real, and become a smoker. (3) The symptoms and the treatment of schizophrenia in this movie are positive symptoms such as delusion and negative symptoms are asociality and alogia. For the treatment, there are two ways in the process treatment, the first way John tried drugs therapy, but it does not work. Second way, he tried to Social and Psychological Treatment, he learnt sociality with environment by meet, greet and talk with people around him and it worked.